Expressive voting versus information avoidance: experimental evidence in the context of climate change mitigation - Momsen, Katharina; Ohndorf, Markus (Public choice, 2023)
We theoretically and experimentally investigate the effect of self-serving information avoidance on moral bias in democratic and individual decisions in the context of climate change mitigation. Subjects choose between two allocations that differ in payoffs and contributions to climate change mitigation. We vary the observability of the environmental contribution, as well as the decision context associated with different levels of pivotality. If the contribution is directly observable, we find evidence for lower pivotality leading to higher levels of “green” decisions, as predicted by the low-cost theory of voting. This effect disappears if subjects can avoid information on the contribution. Instead, we find evidence for the exploitation of moral wiggle room via information avoidance in larger democracies as well as in the consumption context. Our results indicate that information avoidance substitutes expressive voting as an instrument to manage cognitive dissonance on the part of the voter. Hence, moral biases in elections might be less likely than previously thought.
Online veröffentlicht am 31. Dezember 2022
Gesehen am 07.08.2023